Electroacupuncture Therapy for Knee Pain Syndrome of Qi and Blood Stagnation in the ST Meridian - Erlina Cindi Anjaly; Sholichan Badri; Nurtama Aditya Nugraha (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
Knee pain is a joint disease characterized by pain, crepitus, and stiffness in the knee joint. The inflammatory process in knee pain affects the cartilage, synovial fluid, and subchondral bone. Objective: To determine the effectiveness of electroacupuncture therapy with points ST 35 Dubi, EX-LE 4 Neixiyan, GB 33 Xiyangguan, BL 40 Weizhong, LR 8 Ququan, GB 34 Yanglingquan, SP 9 Yinlingquan, BL 55 Heyang, EX-LE 2 Heding, ST 36 Zusanli, SP 10 Xuehai, ST 40 Fenglong, and ST 34 Liangqiu in patients with knee pain. Management of knee pain with electroacupuncture method at points ST 35 Dubi, EX-LE 4 Neixiyan, GB 33 Xiyangguan, BL 40 Weizhong, LR 8 Ququan, GB 34 Yanglingquan, SP 9 Yinlingquan, BL 55 Heyang, EX-LE 2 Heding, ST 36 Zusanli, SP 10 Xuehai, ST 40 Fenglong, and ST 34 Liangqiu. The therapy principle in this case is to smooth the Qi and Xue in the ST meridian. Therapy was performed for 6 sessions. The outcome measurement indicator used the Numeric Rating Scale (NRS). Electroacupuncture therapy for 6 sessions effectively reduced knee pain from a scale of 6 to a scale of 0. Electroacupuncture is effective in reducing pain in patients with knee pain.